2020
DOI: 10.15212/ijafr-2020-0116
|View full text |Cite
|
Sign up to set email alerts
|

The effect of extended post-mortem ageing on the Warner–Brazler shear force of longissimus thoracis from beef heifers from two sire breeds, slaughtered at 20 or 25 mo of age

Abstract: The effects on tenderness of extended ageing of longissimus thoracis (LT, striploin) muscle that differed in structure and composition were examined. Spring-born Angus × Holstein-Friesian heifers (n = 48) and Belgian Blue × Holstein-Friesian heifers (n = 48) were slaughtered, within sire breed, at 20 or 25 mo of age. Approximately 48 h post-mortem, LT steaks (2.5 cm) were removed, and either stored at −20°C for chemical analysis or vacuum-packed, stored at 2°C for 7, 14 or 28 d post-mortem and then at −20°C pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Beef labelled as "Grass-Based or Grass-Fed", which can command a premium price (Stampa et al, 2020), is likely to become more prominent on market shelves. Similarly, there is an increase in early-maturing breed branded beef products in the Irish market place, which also command a premium price (Moloney et al, 2020b). Methods that validate the elements of a system of production are therefore required.…”
Section: Authentication Of Pre-slaughter Diet and Sire Breedmentioning
confidence: 99%
“…Beef labelled as "Grass-Based or Grass-Fed", which can command a premium price (Stampa et al, 2020), is likely to become more prominent on market shelves. Similarly, there is an increase in early-maturing breed branded beef products in the Irish market place, which also command a premium price (Moloney et al, 2020b). Methods that validate the elements of a system of production are therefore required.…”
Section: Authentication Of Pre-slaughter Diet and Sire Breedmentioning
confidence: 99%
“…Regan [ 7 ] reported that concentrate supplementation increased the mean carcass fat score of grazing, LM suckler bulls (from 5.0 to 6.2), whereas the mean fat score of unsupplemented EM grazing bulls (6.33) met the required specification. There is a perception that beef from the progeny of EM sires is of superior eating quality and striploins are often “breed”-branded and attract a premium price [ 8 ]. Meat colour is also an important influence on the purchasing decision of the consumer [ 9 ].…”
Section: Introductionmentioning
confidence: 99%